2015
DOI: 10.1002/mus.24672
|View full text |Cite
|
Sign up to set email alerts
|

Painful cramps and giant myotonic discharges in a family with the Nav1.4‐G1306A mutation

Abstract: Ephaptic transmission between neighboring muscle fibers may not only cause the unusual size of the myotonic discharges in this family, but also a more severe type of potassium-aggravated myotonia than myotonia fluctuans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…At present, no useful guidelines exist on how to clarify the cause of myalgia. 19 Painful cramps or myalgia with myotonia have been reported in a few families with other SCN4A mutations, 2023 but to the best of our knowledge, myalgia without myotonic discharges on EMG has not been reported before. Besides p.A1156T SCN4A mutation, DM2 is an important disorder to be considered in differential diagnostics of myalgic syndromes.…”
Section: Discussionmentioning
confidence: 85%
“…At present, no useful guidelines exist on how to clarify the cause of myalgia. 19 Painful cramps or myalgia with myotonia have been reported in a few families with other SCN4A mutations, 2023 but to the best of our knowledge, myalgia without myotonic discharges on EMG has not been reported before. Besides p.A1156T SCN4A mutation, DM2 is an important disorder to be considered in differential diagnostics of myalgic syndromes.…”
Section: Discussionmentioning
confidence: 85%
“…Another explanation may be that SCN4A mutations have higher rates of myotonia than the next most prevalent gene mutation, CACNA1S, which can cause pain. 8,9 To understand the burden of pain on patients with PP, we compared our survey results with the general population. A study of 472 US subjects evaluated their pain using the WPI and SS scales and were separated into a group with chronic widespread pain, a group with clinically diagnosed fibromyalgia, and a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis revealed that half of the patients with an SCN4A mutation met the criteria for fibromyalgia, which may suggest some overlap between a predominantly myalgic phenotype 25 and the PP phenotype. Another explanation may be that SCN4A mutations have higher rates of myotonia than the next most prevalent gene mutation , CACNA1S, which can cause pain 8,9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(n = 1), SNEL, dies at 20 months from cardiorespiratory arrest p.Phe1298Cys (c.3893T>G) [65] USE with MEX (400 mg) (n = 1), moderate improvement p.Gly1306Ala (c.3917G>C) [33] positive to MEX (600 mg) (n = 2) [66] NR to MEX, ACZ, and CBZ (nd) (n = 1) p.Gly1306Glu (c.3917G>A) [67] NR to MEX (720 mg), oxcarbazepine (nd), and thiazide diuretics (nd), positive to ACZ (500 mg)…”
Section: Randomized Clinical Trials (Class Of Evidence I)mentioning
confidence: 99%